Purinergic Signaling in the Regulation of Gout Flare and Resolution - Li, Xiaoling; Gao, Jie; Tao, Jinhui (Frontiers in Immunology, 2021)
Gout flares require monosodium urate (MSU) to activate the NLRP3 inflammasome and secrete sufficient IL-1β. However, MSU alone is not sufficient to cause a flare. This is supported by the evidence that most patients with hyperuricemia do not develop gout throughout their lives. Recent studies have shown that, besides MSU, various purine metabolites, including adenosine triphosphate, adenosine diphosphate, and adenosine bind to different purine receptors for regulating IL-1β secretion implicated in the pathogenesis of gout flares. Purine metabolites such as adenosine triphosphate mainly activate the NLRP3 inflammasome through P2X ion channel receptors, which stimulates IL-1β secretion and induces gout flares, while some purine metabolites such as adenosine diphosphate and adenosine mainly act on the G protein-coupled receptors exerting pro-inflammatory or anti-inflammatory effects to regulate the onset and resolution of a gout flare. Given that the purine signaling pathway exerts different regulatory effects on inflammation and that, during the inflammatory process of a gout flare, an altered expression of purine metabolites and their receptors was observed in response to the changes in the internal environment. Thus, the purine signaling pathway is involved in regulating gout flare and resolution. This study was conducted to review and elucidate the role of various purine metabolites and purinergic receptors during the process.